IMPLEMENTATION OF A SYSTEM OF DIGITALIZATION OF BUSINESS PROCESSES IS A WAY TOTO EFFECTIVE RESOURCE MANAGEMENT - CHUIENKO, VITALII; TAZETDINOV, VALERII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article is devoted to the study of issues related to the provision of business processes of production with resources and management of this process. The functioning of any enterprise and its development is ensured by resources - first of all, by their availability and the ability to use them rationally. The article considers the concept of resource provision of production and business processes of enterprises, which is fundamental for the successful operation of any enterprise. The views of scholars on the concept of “resource provision” are generalized. It is determined that for the effective functioning of business processes and increasing the competitiveness of enterprise, a system of management of resource provision of enterprise activities should be formed. The main types of resources are defined and characterized, and the structure of the system of resource provision for production is formed. Given that dairy farming is one of the strategic livestock sectors in Ukraine and ensures food security in Ukraine and ensures the food security of the state, the directions of resource management in milk production are considered, since the structure of the resource supply system for each business process is individual. The dynamics of milk production in recent years is analyzed on the basis of statistical observations in recent years. The importance of providing resources at all levels of enterprise management is determined. The digitalization of business processes provides quick access to databases, allows for control and prompt decision-making on the efficient use of resources. The main task of ensuring product competitiveness is to reduce production costs. The digitalization of processes will help optimize revenues and expenses at all levels of production, as reducing resource consumption is only possible with a comprehensive assessment of their costs and identification of ways to use them rationally. This will help the company choose the right direction of resource formation and use, as well as achieve competitive advantages in the economic market.
Keywords: digitalization; resource provision; business process; competitive products; efficiency; dairy farming